Integrating data mining into contextual goal modeling to tackle context uncertaintiesat design time - Farias, Arthur José Rodrigues (2017)
Dissertação (mestrado)—Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Ciência da Computação, 2017.